The duration of bank relationships - Ongena, Steven; Smith, David C (Journal of Financial Economics, 2001)
We analyze the duration of bank relationships using a unique panel data set of listed firms and their banks from the bank-dominated Norwegian market. We find that firms are more likely to leave a bank as the relationship matures. Small, profitable, and highly leveraged firms maintain shorter bank relationships, as do firms with multiple bank relationships. These findings are robust to censoring, alternate specifications for the distribution of relationship duration, and other control variables relevant to the Norwegian market. Overall, our results cast doubt on theories suggesting that firms become locked into bank relationships.